The pH-tunable Oxidase-like Activity of Cerium Oxide Nanoparticles Achieves Sensitive Fluorigenic Detection of Cancer Biomarkers at Neutral pH - Asati, Atul (2011)
The reliable and sensitive detection of cancer-specific biomarkers is important for the diagnosis and treatment of cancer. Hence, detection of these biomarkers has to be reliably and rapidly performed in diverse settings. A limitation of the conventional biomarker-screening method of ELISA is the employment of labile components, such as hydrogen peroxide and horseradish peroxidase. Previously, we reported that nanoceria is able to oxidize various colorimertic dyes at acidic pH, such as TMB and AzBTS, and an assay was designed for screening the folate receptor. Herein, we show that the ability of nanoceria to oxidize a substrate can be tuned by modulating the pH. Results showed that nanoceria can oxidize the non-fluorescent substrate ampliflu, either to the very stable fluorescent product resorufin at pH 7.0 or to the non-fluorescent resazurin at pH 4.0. Based on these findings, we conjugated Protein G to immobilize antibodies on the surface of nanoceria, in order to detect the expression of prototypic cancer biomarkers at pH 7.0, such as the folate receptor and EpCAM. We found that within 3 h, nanoceria identified the expression of the folate receptor and EpCAM on lung carcinoma and breast adenocarcinoma cells respectively. Traditional ELISA had a readout time of 15 h and a higher detection threshold, while requiring multiple washing steps. Considering these results and nanoceria’s ability to oxidize ampliflu to its stable fluorescent product at neutral pH, the use of antibody-carrying nanoceria in the lab and point-of-care molecular diagnostics is anticipated.